Pengaruh Kualitas Pelayanan terhadap Kepuasan Pelanggan dan Loyalitas Pelanggan (Studi Pada Bank BRI Unit Klojen Malang) - Adhita Larasati (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
Abstract: This study aims to determine the effect of service quality on customer satisfaction and customer loyalty. This type of research is explanatory research which explains the causal relationship between the variables through hypothesis testing. This study used a sample of 250 respondents, the respondents were customers of BRI Klojen Unit Malang, aged more than or equal to 18 years. By using a non-probability sampling technique with a purposive sampling method. Direct hypothesis testing is done using a t- test. This analysis uses the Partial Least Square (PLS) test tool and is assisted by SmartPLS 3.0 software to facilitate research. The analysis results obtained in this study are Assurance has a significant effect on customer satisfaction, Reliability has a significant effect on customer satisfaction, tangibles has a significant effect on customer satisfaction, Accessibility has a significant effect on customer satisfaction, and customer satisfaction has a significant effect on customer loyalty. These results indicate that service quality has a significant effect on customer satisfaction and customer loyalty. Keywords: Assurance, Reliability, Tangibles, Accessibility, Customer Satisfaction, Customer Loyalty